Смерть на брудершафт. Летающий слон: роман-кино / Борис Акунин - Акунин Борис (Астрель, 2012)
Экземпляры: аб. ЦБ (23.09.2015) / Инвентарный номер: 2370 / Цена: 172.00 / Авт.знак: А 44 / ГРНТИ: 17 / ББК: 84 (2Рос=Рус)6